2015
DOI: 10.1111/een.12230
|View full text |Cite
|
Sign up to set email alerts
|

Polyandry restores female fertility and paternal effects diminished by inbreeding in Hippodamia convergens

Abstract: 1. The fertility restoration hypothesis posits that polyandry can evolve when female fertility is reduced by matings with related males, but restored by matings with unrelated ones.2. Using a promiscuous ladybird, this hypothesis was tested by mating mature, virgin females twice with sib and non-sib males in all four permutations and observing female fertility. The development of progeny from the first and 10th clutches was also followed to test for differences in paternal effects.3. Mating treatment did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…But the experience of flies under laboratory conditions is inevitably very different from those in wild populations, for example, in terms of population density, food availability, and exposure to parasites/predators. Moreover, laboratory studies of stalk‐eyed flies and other species have utilized virgin males and females in remating assays, in order to standardize prior mating experience (Baker et al., ; Bayoumy, Michaud, & Bain, ; Burdfield‐Steel, Auty, & Shuker, ; Chelini & Hebets, ; Droge‐Young, Belote, Eeswara, & Pitnick, ; Tregenza & Wedell, ). But virgins are rare in nature in species in which males and females readily remate, and this is particularly true of stalk‐eyed flies in which adult fertility persists for many weeks (Rogers et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the experience of flies under laboratory conditions is inevitably very different from those in wild populations, for example, in terms of population density, food availability, and exposure to parasites/predators. Moreover, laboratory studies of stalk‐eyed flies and other species have utilized virgin males and females in remating assays, in order to standardize prior mating experience (Baker et al., ; Bayoumy, Michaud, & Bain, ; Burdfield‐Steel, Auty, & Shuker, ; Chelini & Hebets, ; Droge‐Young, Belote, Eeswara, & Pitnick, ; Tregenza & Wedell, ). But virgins are rare in nature in species in which males and females readily remate, and this is particularly true of stalk‐eyed flies in which adult fertility persists for many weeks (Rogers et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, laboratory studies of stalk-eyed flies and other species have utilized virgin males and females in remating assays, in order to standardize prior mating experience (Baker et al, 2001;Bayoumy, Michaud, & Bain, 2015;Burdfield-Steel, Auty, & Shuker, 2015;Chelini & Hebets, 2016;Droge-Young, Belote, Eeswara, & Pitnick, 2016;Tregenza & Wedell, 2002). But virgins are rare in nature in species in which males and females readily remate, and this is particularly true of stalk-eyed flies in which adult fertility persists for many weeks (Rogers et al, 2006).…”
Section: (C)mentioning
confidence: 99%
“…As such, many animal species that incur particularly high costs of inbreeding depression, from snails to primates, have evolved strategies to avoid inbreeding [ 8 , 9 ]. These include pre-copulatory mechanisms that reduce the probability of mating with kin, such as the asynchronous maturation of the sexes [ 10 , 11 ], the dispersal of individuals from their native group [ 12 15 ], the copulation of females with several males (polyandry) [ 16 18 ] or kin discrimination during mate choice [ 19 , 20 ]. Alternatively, post-copulatory mechanisms can reduce the fertilisation success of inbred matings, such as male-female gamete incompatibility [ 21 , 22 ] or cryptic female choice (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in crickets revealed that CHCs play an important role in assessing the relatedness of mates (Tuni et al, 2013). Among coccinellids, it was reported that in Hippodamia convergens Guerin Meneville egg viability was reduced and developmental duration was extended when they were subjected to sibling matings (Bayoumy, Michaud & Bain, 2015). Studies on C. sexmaculata have reported that they can identify unsuitable males and bias their choice against related males (Saxena, Mishra & Omkar, 2016).…”
Section: Discussionmentioning
confidence: 99%